Firm‐Specific Seniority and Wages - Barth, Erling (Journal of Labor Economics, 1997)
This article studies the relationship between seniority and wages. Micro data with more than one observation from each firm are utilized to single out the seniority effect on wages arising within firms from the total seniority wage effect. The results show that the seniority effect arises within firms, but do not support the human capital explanation of the seniority wage profile. Employees with high levels of firm‐specific on‐the‐job training requirements have less steep wage profiles. The results give some support to the theory of delayed compensation as piece rate workers have negligible returns to seniority.